(untitled) (Journal of Environmental Science and Natural Resources, 2013)
The purpose of this study is to design Hazard Analysis and Critical Control Point (HACCP) plan for potato chips production based on actual conditions in the plant. A specific model has been developed to boost the safety and quality of potato chips product in this plant. The spread of some diseases by unsafe products due to pathogen reported makes it important to pay attention to the potential contamination in potato chips production. The prerequisite programs (PRPs), operational prerequisite programs (OPRPs), hazards, critical control point, preventive measure, critical limits, monitoring procedure and corrective actions have been designed in this HACCP plan. The production process of the product was also analyzed scrupulously for this HACCP plan. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14839 J. Environ. Sci. & Natural Resources, 5(2): 329-338 2012